2016
DOI: 10.1071/he15056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a health video on diabetic retinopathy

Abstract: Issue addressed Indigenous Australians are 14 times more likely than non-Indigenous Australians to develop diabetic retinopathy (DR). Blindness can be prevented in 98% of cases if DR is identified and treated early. While the National Health and Medical Research Council recommend annual screening for Indigenous Australians, screening attendance rates remain low. The objective of this study was to evaluate whether a targeted health promotion intervention improved patient compliance and screening rates. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Ensuring the cultural appropriateness of programs and tailoring program elements to individualised needs is essential to create healthy lifestyle changes. Like the findings of this study, a key component of another study focused on diabetes in the Aboriginal community found that developing content that met healthcare and cultural needs could increase knowledge and screening for diabetic retinopathy 36 …”
Section: Discussionmentioning
confidence: 50%
“…Ensuring the cultural appropriateness of programs and tailoring program elements to individualised needs is essential to create healthy lifestyle changes. Like the findings of this study, a key component of another study focused on diabetes in the Aboriginal community found that developing content that met healthcare and cultural needs could increase knowledge and screening for diabetic retinopathy 36 …”
Section: Discussionmentioning
confidence: 50%
“…In one study in the NT, involving an Indigenous Elders committee was found to improve integrated chronic disease services; another NT study described the assistance of Indigenous interpreters in translating trachoma control surveys in schools . Interpreting assistance provided by AHWs during the development of a health promotion video improved knowledge about diabetic retinopathy in 27 of 84 Indigenous patients in Western Australia …”
Section: Resultsmentioning
confidence: 99%
“…Consulting AHWs, community members, and Indigenous consultative group members provided support for health promotion by designing materials or strategies regarding trachoma, visual impairment, and diabetic retinopathy that ensured cultural and linguistic appropriateness. Several studies noted that the support of AHWs, school staff, and family members were integral to trachoma control programs, including delivering and maintaining hygiene information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal resources have been allocated to improving access to Indigenous interpreter services, inhibiting regular use 38. From a grassroots perspective, health promotion focused on knowledge gaps with respect to diabetic retinopathy is needed, and may be adapted from existing resources 39. Participants indicated health promotion resources should be delivered in non-text-based form, incorporating Indigenous ways of being, knowing and doing as reported in other settings 40 41.…”
Section: Discussionmentioning
confidence: 99%